2017
DOI: 10.1007/s11356-017-8978-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of streptomycin in aquatic environment: kinetics, pathway, and antibacterial activity analysis

Abstract: Streptomycin used in human and veterinary medicine is released into the environment mainly through excretions. As such, its elimination in water should be investigated to control pollution. In this study, the degradation of streptomycin in water was studied, and the influence of variables, including light exposure, solution pH, temperature, ionic strength, dissolved organic matter (DOM), and coexisting surfactants, on degradation was investigated. Streptomycin degradation was consistent with the first-order mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The half-life of streptomycin was determined to be nearly 105, 42, and 30 days at 15, 25, and 40 • C, respectively, implying a decreased rate of degradation when compared to oxytetracycline. A description of the possible degradation products of oxytetracycline and streptomycin are available (Xuan et al, 2010;Shen et al, 2017). Our results showing a faster loss of efficacy for oxytetracycline than streptomycin upon sunlight exposure are therefore in agreement with the reported degradation kinetics of these antibiotics.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The half-life of streptomycin was determined to be nearly 105, 42, and 30 days at 15, 25, and 40 • C, respectively, implying a decreased rate of degradation when compared to oxytetracycline. A description of the possible degradation products of oxytetracycline and streptomycin are available (Xuan et al, 2010;Shen et al, 2017). Our results showing a faster loss of efficacy for oxytetracycline than streptomycin upon sunlight exposure are therefore in agreement with the reported degradation kinetics of these antibiotics.…”
Section: Discussionsupporting
confidence: 89%
“…Several reports on degradation kinetics and mechanisms of degradation of the antibiotics that are discussed here are available (Wang and Yates, 2008;Xuan et al, 2010;Slana and Dolenc, 2013;Liu et al, 2015;Shen et al, 2017;Leal et al, 2019a,b;Li et al, 2019b;Choi et al, 2020). It has been reported that the half-life of oxytetracycline at 25 • C is approximately 7 days, at 35 • C is 3 days and at 60 • C is 0.2 day, indicating a rapid temperaturedependent degradation of oxytetracycline, as the half-life at 4 • C is 120 days (Xuan et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even though streptomycin can degrade in the environment under the effect of light and temperature among other things, all three streptomycin concentrations used in this were previously reported in environmental surveys (Shen et al. 2017 ). Again, approximately 80% of media was exchanged daily for sterile 1 × E3 media with the relevant antibiotic concentration when applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that streptomycin can persist in aquatic environments for some time and its degradation products still maintain certain antibacterial activity (Shen et al, 2017). On the other hand, selection of Sm R bacteria in in vitro evolution experiments with low concentrations of antibiotic has been observed even after only 96 h (Spagnolo et al, 2015).…”
Section: Prevalence Of Resistance To Individual Antibiotics Among Ap mentioning
confidence: 99%